Tingkat Motivasi Belajar Murid melalui Gamifikasi dalam Manajemen Kelas - Intan Tri Utami; Sri Marmoah; Supianto Supianto (Universitas Sebelas Maret, 2026)
Elementary school students' learning motivation needs to be strengthened through classroom management that is engaging and orderly, and that provides positive reinforcement. This study aims to describe students' learning motivation levels following the implementation of gamification in classroom management. A quantitative approach with a quasi-experimental design was employed. The sample consisted of 54 fifth-grade students: 32 in the experimental group and 22 in the control group. Data were collected using a Likert-scale learning motivation questionnaire and analyzed descriptively, supported by N-Gain and effect size calculations. The mean post-test score for learning motivation in the experimental group was 85.03, higher than the control group's score of 73.00. In the experimental group, 25 students fell into the high category and 7 into the medium category, with no students in the low category. The experimental group's N-Gain of 0.635 and Cohen’s d of 1.027 indicate a strong improvement and effect. Gamification elements such as points, badges, leaderboards, and challenges can serve as classroom management strategies to foster a learning environment that is active and enjoyable, thereby supporting elementary students' learning motivation.